Higher education grant system and challenges in Pakistan: a brief review - Abbas, Zaheer; Ahmad, Abd Rahman; Ng, Kim-Soon; Mohd Adi, Mohd Nazir (American Scientific Publishers, 2018)
This paper discusses about the background of higher education system, grant distribution system and its related issues and challenges at higher education institutions in Pakistan. Accordingly, higher education is considered as a broad horizon of vision which explores the possibilities and offers awareness to new doors for development. In this study, briefed literature based on recently published work by higher education commission of Pakistan has been and concluded. As per overall results, the government of Pakistan does not give preference for the increment of education budged due to national security and terrorism in the country. While, higher education commission of Pakistan has taken sufficient and effective measures for the enhancement of the system of higher education institutions in Pakistan. Moreover, higher education commission of Pakistan also focused for the development of research culture in public privet universities. In, conclusion, this research paper provides the detailed indication of grant distribution system and education policies along with associated issues in Islamic republic of Pakistan.